Self-Reflexive Engagements and Intellectual Pathways in African Philosophy - Mungwini, Pascah (Phronimon, 2025)
Philosophy is self-reflexive when it is able to turn attention back on itself and to take into consideration the place out of which the activity of philosophical engagement is undertaken. In so doing, it allows itself the opportunity to develop inner strength and to define new intellectual pathways always in response to the real issues confronting society. In this article, the focus is on African Philosophy and on the following specific question: What ought to be the defining character of the practice in the contemporary circumstances in which we find ourselves, and for what reason? The concern is not just a normative one but an attempt to redirect philosophy to its original destination, to the very place within which questions of ethics and politics arise. It is about defining more promising pathways and nodes of intellectual engagement for African Philosophy. There are priority issues that impose themselves on the philosophical practice in Africa, and these deserve our attention. Ultimately, the intellectual pathways that African Philosophy may take will only be limited by our capacities to imagine what is possible.